Efeito Peltier em estruturas semicondutoras quasiperiódicas - Gomes, Reben Rudson Mendes (2008)
There is nowadays a growing demand for located cooling and stabilization in optical and electronic devices, haul of portable systems of cooling that they allow a larger independence in several activities. The modules of thermoelectrical cooling are bombs of heat that use efect Peltier, that consists of the production of a temperature gradient when an electric current is applied to a thermoelectrical pair formed by two diferent drivers. That efect is part of a class of thermoelectrical efcts that it is typical of junctions among electric drivers. The modules are manufactured with semiconductors. The used is the bismuth telluride Bi2Te3, arranged in a periodic sequence. In this sense the idea appeared of doing an analysis of a system that obeys the sequence of Fibonacci. The sequence of Fibonacci has connections with the golden proportion, could be found in the reproductive study of the bees, in the behavior of the light and of the atoms, as well as in the growth of plants and in the study of galaxies, among many other applications. An apparatus unidimensional was set up with the objective of investigating the thermal behavior of a module that obeys it a rule of growth of the type Fibonacci. The results demonstrate that the modules that possess periodic arrangement are more eficient